Análisis de la contribución solar para lograr participación del 20% a partir de fuentes renovables en la canasta eléctrica colombiana 2030 (2017)
This degree project seeks the maximum contribution of solar energy to contribute to a possible installation of 20% of renewable sources in Colombia in 2030, considering solar photovoltaic technology. It seeks the evaluation and feasibility of scenarios that include a participation of solar energy within the forecast for 2030 in the energy basket. Each scenario will be studied, analyzing the costs, viability by solar radiation, installed capacity, technicians, among others.